Preparedness and challenges of police in using forensic science: a review of some related literature / Zakariyya Sarki and Geshina Ayu Mat Saad - Sarki, Zakariyya; Mat Saad, Geshina Ayu (Universiti Teknologi Mara Cawangan Pulau Pinang, 2018)
This article is a review of studies related to the application of forensic science in crime prevention and control. The aim was to summarise the preparedness and challenges of the police in the utilization of forensic science in crime prevention and control as reported by the studies. The article was also aimed at reviewing the various methods used by the studies. Systematic review was used as a method to achieve the aims. Fourteen articles were selected and reviewed. It was found that some of the literature reported on factors influencing preparedness of the police in using forensic science; others identified the lingering challenges faced by forensic science practitioners, police inclusive; while some of the literature reported both. However, most of the literature reviewed made no reference to any international standard guidelines in determining the preparedness; also, the methods adopted by most of the studies were not rigorous. Consequently, future research on preparedness and challenges of police in using forensic science should have frameworks of guidelines and adopt more suitable research methods.